Material responses to natural hazards in 16th and 17th centuries - Zwitter, Žiga (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Material responses to natural hazards threatening agricultural land and dwellings in princely seigneuries and urban settlements included cooperation between central agencies, regional and local level % in some cases leading to efficient measures. Examples of reactions of provincial estates, non-princely seigneuries and neighbours are also given. Historical knowledge contributed to risk mitigation. Artificial interventions in landscape due to flood hazard affected also flood safe locations.
Keywords: 16./17.st.; arhivsko gradivo; Carniola; elementarne nesreče; Kranjska; kulturna pokrajina; naravne nesreče; Slovenia; Slovenija; zgodovinski pregledi